Hydraulic Valve Failure Analysis at MT. Beyond Using the FMEA Method - Muslihati Hasan; Arif Fuddin Usman; Andi Ningrat; Rifkah Fitriah; Muhammad Aris Kastian (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Hydraulic valve failure on a tanker can significantly impact operational performance and shipping safety. This study aims to analyze the causes, impacts, and solutions to hydraulic valve failure on the MT. Beyond. The method used was a qualitative descriptive approach, with data collection techniques through observation, interviews, and documentation studies. Data analysis was performed using the Fishbone Diagram method to identify root causes and Failure Mode and Effects Analysis (FMEA) to evaluate the level of failure risk based on severity, occurrence, and detection parameters. The results showed that hydraulic valve failure was influenced by human, machine, material, method, and environmental factors, with the dominant causes being operational errors, low component quality, fluid contamination, and lack of maintenance. The FMEA analysis showed that the key components with high risk were the disc and seat, which had the highest Risk Priority Number (RPN) values of 162 and 132, respectively. Failure of these components can cause uncontrolled flow, potentially reducing overall system performance due to corrosion, leakage, and wear,thus becoming the main priority for repair. The conclusion of this study confirms that improving component quality, regular maintenance, operator training, and implementing an effective monitoring system can reduce the risk of failure and increase the reliability of the ship's hydraulic system.